(1372) التحليل الكمى كمدخل لتخطيط الموارد البشرية Quantitative analysis as an approach to human resource planning - نبيل الحسيني النجار (معهد التخطيط القومى, 2026)
تناقش هذه الدراسة أهمية استبدال الأساليب التقليدية القائمة على "الخبرة والحدس" بأساليب كمية وعلمية دقيقة لتخطيط الموارد البشرية في قطاع البترول، تركز الدراسة التطبيقية المقارنة على ثلاثة نماذج لشركات في مصر والسعودية (شركة السويس لتصنيع البترول، وشركتي بترولاين وبترولوب السعوديتين)، وذلك خلال الفترة من 1971 إلى 1980 تهدف الباحثة من خلال هذا المدخل إلى إيجاد علاقات رياضية تربط بين حجم "قوة العمل" كمتغير تابع، ومجموعة من المتغيرات المستقلة مثل (حجم وقيمة الإنتاج، كمية وقيمة المبيعات، الأجور المنصرفة، ورأس المال المستثمر)، لضمان الاستخدام الأمثل للموارد البشرية وتلبية احتياجات التشغيل الفعلية. استخدمت الدراسة نماذج الانحدار الخطي وغير الخطي (البسيط والمتعدد) لتحليل البيانات آلياً عبر الحاسب الإلكتروني، وأظهرت النتائج وجود علاقة ارتباط طردية قوية في أغلب الحالات، خاصة بين عدد العاملين والأجور والإنتاج (، ومن النتائج اللافتة، كشفت الدراسة عن علاقة عكسية في إحدى الشركات السعودية بين زيادة رأس المال المستثمر وعدد العمالة، وهو ما أرجعه الباحث إلى التوسع في استخدام "الآلية" (Automation) والإحلال التكنولوجي الذي يقلل الاعتماد على العمالة المباشرة، وتخلص الدراسة إلى أن اعتماد هذه النماذج الرياضية يساهم بفاعلية في ترشيد قرارات المخططين وتوقع الاحتياجات المستقبلية من القوى العاملة بدقة أعلي. This study discusses the importance of replacing traditional, experience-based, and intuitive approaches to human resource planning in the petroleum sector with precise quantitative and scientific methods. The comparative applied study focuses on three company models in Egypt and Saudi Arabia (Suez Oil Processing Company, and the Saudi companies Petroline and Petrolub) during the period from 1971 to 1980. Through this approach, the researcher aims to establish mathematical relationships linking the size of the workforce (as a dependent variable) to a set of independent variables, such as production volume and value, sales volume and value, wages paid, and invested capital, to ensure the optimal use of human resources and meet actual operational needs. The study used linear and non-linear regression models (simple and multiple) to analyze the data automatically via computer. The results showed a strong positive correlation in most cases, especially between the number of workers, wages, and production. Among the notable results, the study revealed an inverse relationship in one of the Saudi companies between the increase in invested capital and the number of workers, which the researcher attributed to the expansion in the use of automation and technological replacement that reduces reliance on direct labor. The study concludes that adopting these mathematical models effectively contributes to rationalizing the decisions of planners and predicting future labor needs with greater accuracy.